2015
DOI: 10.1128/mbio.01180-15
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Hepatovirus ( Phopivirus of Seals) Related to Human Hepatitis A Virus

Abstract: Describing the viral diversity of wildlife can provide interesting and useful insights into the natural history of established human pathogens. In this study, we describe a previously unknown picornavirus in harbor seals (tentatively named phopivirus) that is related to human hepatitis A virus (HAV). We show that phopivirus shares several genetic and phenotypic characteristics with HAV, including phylogenetic relatedness across the genome, a specific and seemingly quiescent tropism for hepatocytes, structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 33 publications
2
49
0
3
Order By: Relevance
“…Although these results are of importance, mammals and birds represent only a small proportion (less than 25%) of total number of vertebrates, and little is known about the natural viromes of the vast number of vertebrate species. Indeed, recent metagenomic studies [6][7][8][9][10][11] suggest that our understanding of the true biodiversity and evolution of vertebrate RNA viruses is limited, fragmentary and biased.…”
Section: Introductionmentioning
confidence: 99%
“…Although these results are of importance, mammals and birds represent only a small proportion (less than 25%) of total number of vertebrates, and little is known about the natural viromes of the vast number of vertebrate species. Indeed, recent metagenomic studies [6][7][8][9][10][11] suggest that our understanding of the true biodiversity and evolution of vertebrate RNA viruses is limited, fragmentary and biased.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 A plethora of HAV-related viruses were recovered from various mammalian species during 2015-2018, including predominantly bats and rodents, but also tree shrews, seals and marsupials. [25][26][27][28][29] HBV-related viruses were detected in bats during 2013-2015 30,31 and in a domestic cat in 2018. 32 A distinct HBV species termed capuchin monkey hepatitis B virus (CMHBV) was described in 2018.…”
Section: A New Era Of Virus Discoverymentioning
confidence: 99%
“…However, this "prejudice" has already been challenged and overturned by animal model engineering as well as by new scientific discoveries. In 2015, several strains of human HAV have been found in seals, which may indicate that the first natural nonprimate HAV to be discovered, and provide further understanding for the evolutionary history and pathogenicity of HAV [98]. Moreover, in recent years, HAV-associated hepatoviruses have been found in bats, rodents, hedgehogs [38], duck [99][100][101], and woodchucks [102,103], which suggested that there may be more candidate animals potentially used as animal models of HAV.…”
Section: Other Animal Modelsmentioning
confidence: 99%